Healing Acupressure Lr-3 on Blood Pressure and Anxiety Levels in Pregnant Women with Hypertension - Dina Indrati Dyah Sulistyowati (Eduvest - Journal of Universal Studies, 2022)
Hypertension pregnancy disorders are one of the causes of increased morbidity and mortality of maternal, fetal, and neonates. The maternal mortality rate (MMR) in Indonesia is still quite high. One of the causes of maternal death is hypertension. Healing acupressure LR 3 is a combination of self-healing and acupressure, where the massage process has 2 reactions, namely the strengthening reaction (yang) and the lowering reaction (yin). Massages at a certain point in acupressure therapy can stimulate nerve waves so that they can launch blood flow, relax spasms, and lower blood pressure. This study aims to determine the effectiveness of healing acupressure LR-3 (healing-pressure) affects blood pressure and anxiety levels in pregnant women with hypertension, compare pre-test control groups and experiments, compare pre-and post-test in control and experimental groups, and compare the differences in pre-post tests between control groups and experiments. Research including experiment, using the randomized pre-test post-test control group design research design. The analysis used a repeated ANOVA test with post hoc Bonferroni.The results of this study are expected to be an operational standard in helping to increase knowledge to overcome pregnant women with hypertension in a non-pharmacological manner that is safe for mothers and babies. The results of the analyzed are found that there was a significant difference in the average blood pressure and anxiety level of pregnant women after being given intervention in the intervention group before and after the intervention period (p < 0.000), meaning that there was an effect of healing acupressure LR-3 (healing-pressure) affecting blood pressure and anxiety levels in pregnant women with hypertension.